Challenging structures: gender transformative interventions by livestock CRP in Ethiopia - Kinati, Wole; Temple, Elizabeth C.; Baker, A. Derek; Najjar, Dina (Frontiers Media, 2023)
Introduction: This study is a review of secondary literature that has been synthesized to extract information and demonstrate the implementation and impact of community conversations (CCs) on gender aspects of social norms in livestock-based systems in Ethiopia. Methods: The study used the phenomenological method of qualitative literature review to sketch the gender transformative approach to the delivery of knowledge products in a program on transforming the small ruminant value chain. The CC aimed at addressing gender-related norms in the division of labor, resource ownership, and handling practices of animals and their products previously identified, and those that emerged during the CC events across the study sites. A total of 1,517 community members (out of which 574 are women) took part in various CC events. Results and discussion: The review shows that the gender-related norms addressed were in line with the identified constraining norms faced by women livestock keepers in the mixed and livestock-based systems. The CC approach adopted complied with the stages laid out in literature: identification of existing knowledge; imparting new knowledge; knowledge integration and application; and review, reflection, and re-planning. The process was inclusive and community-engaging, which possibly cultivated intrinsic motivation and ownership of the process. Changes in knowledge, attitudes, and practices at household, community, and institutional levels were identified. The conclusions include institutionalizing the gender transformative approach in the public agricultural extension system. This could be facilitated by the generation of robust objective evidence of impacts and guidance for subsequent scaling at local, regional, and national levels,